Prevalence of Low Bone Density and Comorbid Hypogonadism in Patients With Chronic Pancreatitis. Issue 3 (March 2019) - Gupta, Namita; Singh, Shailender; Vargas, Luciano; Moore, Timothy E.; Shostrom, Valerie K.; Boerner, Brian P.
Abstract : Objectives: Patients with chronic pancreatitis (CP) are at increased risk of low bone mineral density (BMD), although the prevalence of low BMD in patients with CP in the United States is lacking. We aimed to determine the prevalence of low BMD and identify potential risk factors, including hypogonadism and use of opioid medications, in subjects with CP in the United States. Methods: This was a prospective, observational study. Subjects with CP underwent dual-energy x-ray absorptiometry scan. Blood was assayed for vitamin D, sex hormones, and a metabolic panel. History was obtained for fractures, menopause, hypogonadal symptoms, and opioid medication doses. Low BMD was defined by both World Health Organization and the International Society for Clinical Densitometry criteria. Results: Depending on criteria used, 37% to 55% of our cohort had low BMD. Subjects with low and normal BMD had similar vitamin D levels. Hypogonadism was present in 27% of nonmenopausal subjects and was associated with reduced lumbar spine BMD in subjects 30 years or older. Conclusions: Patients with CP are at increased risk of low BMD, which is likely multifactorial. Hypogonadism, possibly related to opioid pain medications, may be an independent risk factor for low BMD in CP.